2012
DOI: 10.1159/000338090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Subthalamic Nucleus Deep Brain Stimulation on the Autonomic Nervous System in Parkinson’s Disease Patients Assessed by Spectral Analyses of R-R Interval Variability and Blood Pressure Variability

Abstract: Objective: Autonomic nervous system impairment is an untoward symptom that is typically observed in advanced Parkinson’s disease (PD) patients. However, details of the effects of subthalamic nucleus deep brain stimulation (STN-DBS) on the autonomic nervous system remain unclear. Methods: Twenty-eight patients with advanced PD (12 males and 16 females) who underwent bilateral STN-DBS and 13 age-matched healthy controls were included in this study. We analyzed the dynamic cardiovascular autonomic function regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Deep brain stimulation employs chronically implanted electrodes in the brain to electrically stimulate neuronal networks (Albert et al., 2009), and has also been shown to increase CVC (Sumi et al., 2012).…”
Section: Main Textmentioning
confidence: 99%
“…Deep brain stimulation employs chronically implanted electrodes in the brain to electrically stimulate neuronal networks (Albert et al., 2009), and has also been shown to increase CVC (Sumi et al., 2012).…”
Section: Main Textmentioning
confidence: 99%
“…76 Another controlled study including 28 PD patients proposed that the vagal component of the arterial-cardiac baroreflex improved postoperatively. 77 Dafsari et al . 23 suggested that STN DBS may have a long-term effect on cardiovascular symptoms, and opine that further studies are needed.…”
Section: Dbs Effect On the Autonomic Domainmentioning
confidence: 99%
“…Several other publications also offer conflicting opinions on the cardiovascular effects of STN DBS [ 38 , 39 , 40 ]. Sumi et al [ 41 ] imply that the cardiovascular improvements seen with STN DBS are due not to the stimulation itself, but rather to an increased ability to exercise, thus improving overall cardiovascular health and lower extremity muscle strength. One explanation for the conflicting reports may be that the autonomic effects are not a direct result of the stimulation at all, but are rather the result of reduced need for pharmacotherapy to combat motor symptoms of PD [ 42 ].…”
Section: Sympathetic Autonomic Modulationmentioning
confidence: 99%